NEW DATA ON PI+PI- ANGULAR-DISTRIBUTION IN MASS RANGE 0.8-2.2 GEV-C2 - Corden, M; Dowell, J; Garvey, J; Jobes, M; Kenyon, I; Mawson, J; Mcmahon, T; Corbett, I; Esterling, R; Lipman, N; Litchfield, P; Sumorok, K; et al. (1978)
An experiment has been performed on the Omega spectrometer to study the channel π-p → π+π-n at 12 and 15 GeV/. The π+π- angular distribution has been studied in the π+π- invariant-mass region 0.8-2.2 GeV/c2, for events with four-momentum transfer squared from proton to neutron in the range -0.02 to -0.15 (GeV/c)2. The spherical harmonic moments of the angular distribution are presented. Up to a mass of 1.7 GeV/c2 the moments agree with previous experiments. At higher masses Y70, Y80 and Y90 are non-zero and indicate the presence of ππ amplitudes with spin greater than 3. © 1978.